2021
DOI: 10.1111/hex.13381
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of substitute decision‐makers and staff about person‐centred physical activity in long‐term care

Abstract: Introduction: This paper aims to explore the care processes that best exemplify personcentred care during physical activity (PA) for long-term care (LTC) residents with dementia from the perspectives of substitute decision-makers (SDMs) and LTC home staff. Little is known about how person-centred care is reflected during PA for residents with dementia, or the barriers and benefits to enacting person-centred care during PA. Methods: Semistructured interviews were used to collect SDMs and LTC home staffs' perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that that older adults have a positive attitudes towards using smart technologies to help maintain health, independence and communication (Choi et al, 2021). However, the implementation of technology in long‐term care (LTC) settings is complex due to the need for staff assistance and the added workload it creates (Chu, Quan, et al, 2021). While the use of assistive technology in community settings for older adults has been studied (Choi et al, 2021; Lee, 2014; Skubic et al, 2016; Tural et al, 2021), the feasibility and acceptability of implementing of using such technology in LTC settings remains an under‐researched area (Pappadà et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that that older adults have a positive attitudes towards using smart technologies to help maintain health, independence and communication (Choi et al, 2021). However, the implementation of technology in long‐term care (LTC) settings is complex due to the need for staff assistance and the added workload it creates (Chu, Quan, et al, 2021). While the use of assistive technology in community settings for older adults has been studied (Choi et al, 2021; Lee, 2014; Skubic et al, 2016; Tural et al, 2021), the feasibility and acceptability of implementing of using such technology in LTC settings remains an under‐researched area (Pappadà et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, we consider who is in spaces for sharing decisions about research, services and policy in this special issue. There are papers with lead authors from seven countries: the United Kingdom, [22][23][24][25][26][27][28] Australia, [29][30][31][32][33] Canada, [34][35][36][37][38] the United States, 39,40 the Netherlands, 41,42 France 43 and Ecuador. 44 There are important examples involving people who experience homelessness, 22,23,34 people who have disabilities, 26,41,42 people who live in socioeconomically disadvantaged circumstances 35,37 and people who are migrants and/or from ethnic minority groups.…”
mentioning
confidence: 99%